Immune Response Induced by Carbomer Adjuvanted Equine Influenza Vaccine - Madkour, Nashwa K.; Ebied, Eman M.; Saleh, Nehal S.; Warda, Fatma F.; Aly, Naglaa I. (Journal of Advanced Veterinary Research, 2023)
Vaccination against Equine influenza virus (EIV) is necessary to minimize and prevent spreading of the disease. There are many types of natural and synthetic adjuvants which can improve the efficacy of animal vaccines, such as aluminum compounds, emulsions, saponins, and carbomer. The current study was carried out to compare inactivated Equine influenza vaccines containing carbomer as an adjuvant in concentrations of 0.25% and 0.50% (formula 2&3) with an inactivated vaccine containing a combination of aluminum hydroxide gel and saponin as a conventional adjuvant (formula 1). The potency of the different vaccine formulations was tested in groups of guinea pigs. The mean HI- antibodies titer 3 weeks post inoculation of group (A) with formula-1, group (B) with formula-2 and group (C) with formula-3 were 9.2 log2, 10.4 log2 and 10.6 log2. All formulae were potent with higher HI antibodies in group B compared to group A. Groups B and C had nearly the same results. Stability testing of the prepared vaccines (formula 1&2) proved that both formulae were potent and stable at 40C for two years. Seroconversion of the prepared vaccines (formula 1&2) in horses revealed that EI vaccine adjuvanted with carbomer induced higher HI-antibodies titer as well as longer lasting immune response in horses than those induced by combination of aluminum hydroxide gel & saponin.